The Positive Impact of the Family State Program on the Social Status of Large Families and the Encouragement of Birth in Georgia - Lazishvili, Sophio (European Scientific Journal, ESJ, 2023)
Georgia belongs to a country with a small population, where one of the country’s social challenges is the issue of population demography. Despite the fact that the country has one of the strongest social support state programs, which includes measures to support citizens, measures to support demography, birth rate, and large families are underrepresented in it. The article discusses the issues of solving demographic challenges in Georgia, effective implementation of family policy and introduction of incentive mechanisms for large families. The purpose of Nashom’s research is to determine the role of state support policies and identify gaps based on the study of challenges related to the birth rate, encouragement and support of large families, demographic process. Introduction of recommendations for the improvement of demography and the state policy supporting large families in Georgia. Mixed-quantitative and qualitative research methods were used to carry out the research, and general research methods were used for data processing. As a result of analyzing the studied international scientific literature, statistical and scientific studies, legislative packages, the state policy of support for large families operating in Georgia, challenges and mechanisms for strengthening the state policy of support for large families were highlighted. The recommendations obtained as a result of the studied scientific material and the conducted research will support and improve the state policy of supporting large families in Georgia and will have a positive impact on demographic issues. The article will be interesting for representatives of the legislative and executive authorities, political entities, public administration specialists and experts.